Effect of graphite addition on dry sliding wear behavior of Self-lubricating Al-SiC-Gr hybrid composites by PM process. (2022) - Ravindran, P.; Jinnah Sheik Mohamed, M.; Joe Patrick Gnanaraj, S.; Appadurai, M.
Abstract: The effect of graphite content and material connected parameter on the wear behavior of Al hybrid composite was studied using factorial design. Wear tests were conducted by variable Gr content (5 and 10 wt%) at totally different sliding speeds (1.5 and 3 m/s) and sliding distances (1500 and 3000 m). statistical modeling was used to develop a mathematical relationship on wear below varying conditions of sliding speed, applied load, and sliding distance. The created numerical model showed that high Gr content composite was subject to a low wear loss compared to that of low Gr composite. Increase of speed decreases the damage and increase either load or sliding distance or each will increase the wear loss. The simplest wear resistance is achieved within the hybrid composite containing 10 wt. %Gr particles.